Effect of glycophosphopeptide on the lymphocytes and IgA of Olympic platform divers - Muñoz-Soria, E.; Reséndiz-Albor, A. A.; Osorio-Victoria, M. L.; Ramirez-Garcia, C.; Moreno-Lafont, M. C.; Rivera-Aguilar, V.; Campos-Rodriguez, R. (The Journal of Sports Medicine and Physical Fitness, 2012)
AIM: The aim of this paper was to evaluate the effect of a treatment with glycophosphopeptide on Olympic high platform divers during training and competition by measuring lymphocytes and cortisol in peripheral blood, and secretory immunoglobin A in saliva (sIgA). METHODS: Two groups of 8 divers were given a 14-day treatment of capsules (Gp or placebo) three times per day. Measurements of the peripheral blood lymphocytes (TCD3+, TCD4+ and T CD8+), plasma cortisol and IgA levels in saliva were made on day 0, 21 and 150. RESULTS: There was no significant difference found between the Gp- and placebo-treated groups regarding the increase in IgA between basal and first, or first and second measurements. The fact that there was a significant increase in S-IgA (9.89±0.44 to 10.59±0.55, P=0.001) and B CD19+ (345.13±108.24 to 484.75±120.54, P=0.025) in the Gp- and not in the placebo-treated group between the basal and first measurement was due to the variation among the athletes of the latter group, and not the increase itself, indicating that Gp acted as an immunomodulator. It was apparently the exercise and not the Gp treatment that caused the increase in S-IgA and B CD19+ at the first and second measurements. CONCLUSION: The current study reports that with athletes who practiced moderately intense exercise, which stimulated the immune response, a Gp treatment of two weeks seems to have acted only as an immunomodulator that reduced the variation in the increased levels of IgA and B CD19+.